2021
DOI: 10.3390/cells10061435
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated Poly-l-Lysine as a Macromolecular Cryoprotective Agent Enables the Development of Defined and Xeno-Free Human Sperm Cryopreservation Reagents

Abstract: In human sperm cryopreservation, test yolk buffer and human serum albumin have been used as permeating macromolecular-weight cryoprotectants. In clinical reproductive medicine, human serum albumin is frequently used because of low risks of zoonoses and allergic reactions. However, the risk of allogeneic infectious diseases exists, and the supply may be unstable because human serum albumin is derived from human blood. Therefore, the development of xeno-free human sperm cryopreservative reagents that could overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The most suitable concentration of CPLL in the presence of 3% glycerol for pig spermatozoa was 0.25%, whereas the most suitable concentration of CPLL in the presence of 3.25% glycerol for bovine spermatozoa was 0.5% [ 11 ]. Moreover, the most suitable concentrations of CPLL have been reported to be 0.75% in the presence of 5% glycerol for buffalo spermatozoa [ 12 ], 0.3% in the presence of 7% glycerol for human spermatozoa [ 14 ] and 1% in the presence of 8% DMSO for rabbit spermatozoa [ 13 ]. These results suggest that the optimal concentration of CPLL for cryopreservation of spermatozoa varies with the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most suitable concentration of CPLL in the presence of 3% glycerol for pig spermatozoa was 0.25%, whereas the most suitable concentration of CPLL in the presence of 3.25% glycerol for bovine spermatozoa was 0.5% [ 11 ]. Moreover, the most suitable concentrations of CPLL have been reported to be 0.75% in the presence of 5% glycerol for buffalo spermatozoa [ 12 ], 0.3% in the presence of 7% glycerol for human spermatozoa [ 14 ] and 1% in the presence of 8% DMSO for rabbit spermatozoa [ 13 ]. These results suggest that the optimal concentration of CPLL for cryopreservation of spermatozoa varies with the species.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the cellular stress may be responsible for cryoprotection [ 9 ]. Recent studies have shown that CPLL is also effective for cryopreservation of germ cells such as pig embryos at the pronuclear stage [ 10 ] and bovine, buffalo, rabbit, and human spermatozoa [ 11 , 12 , 13 , 14 ]. In the present study, we investigated the efficacy of CPLL as a cryoprotectant for pig spermatozoa.…”
mentioning
confidence: 99%
“…Therefore, CPLL could be applied as a substitute for TYB and HSA, which are currently used in human sperm cryopreservation reagents. Our developed human sperm cryopreservation reagent containing CPLL showed comparable performance to HSA-containing sperm cryopreservation reagents upon evaluation of sperm properties, including motility rate and fertilization ability after freezing and thawing; furthermore, it has been suggested that CPLL may reduce sperm DNA fragmentation (SDF), which has recently been the focus of attention [9]. Our novel human sperm cryopreservation reagent had a different composition than the commercially available cryopreservation reagent used as a control, making it unclear whether the reduction in SDF was due to the protective property of the CPLL or not.…”
Section: Introductionmentioning
confidence: 95%
“…HSA-containing sperm cryopreservation reagents are now widely used in clinical practice; however, they are associated with lot-to-lot variation during manufacturing, the risk of allogeneic infections, and unstable supply. To address these problems, we developed the world's first animalcomponent-free human sperm cryopreservation reagent using a chemical compound, carboxylated poly-L-lysine (CPLL), as a substitute for animal-derived components [9].…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylated poly‐L‐lysine (CPLL) is an ampholytic polymer compound obtained by synthesizing an aqueous solution of ε‐poly‐L‐lysine and succinic anhydride, followed by the conversion of 65 mol% of the amino groups to carboxyl groups (Matsumura & Hyon, 2009; Matsumura et al, 2021). As CPLL has been shown to be effective for the cryopreservation of germ cells, such as porcine embryos at the pronuclear stage (Kamoshita et al, 2017) and bovine, buffalo, rabbit, and human spermatozoa (Fujikawa et al, 2018; Küçük et al, 2021; Takeuchi et al, 2021; Tariq et al, 2020), we investigated the efficacy of CPLL as a cryoprotectant for porcine spermatozoa in a previous study (Jin et al, 2022). The findings showed that the addition of CPLL to a glycerol‐containing freezing extender improved the motility of frozen‐thawed porcine spermatozoa and the in vitro development of embryos produced by in vitro fertilization.…”
Section: Introductionmentioning
confidence: 99%